Noise prevention strategies among neonatal intensive care unit nurses: a qualitative study - Günay Arslan; Özge Eren; Çağrı Çövener Özçelik (BMC Nursing)
Abstract Background Noise is a condition that harms newborns. There are studies on the effect of noise on the newborn, but not enought there are studies on how the noise is prevented by the nurses. Purpose This study was conducted to examine the knowledge, attitudes and methods used by nurses to prevent noise in the Neonatal Intensive Care Unit (NICU). Methods The study carried out as qualitative phenomenological design research, the study took place between September-November 2021 with 12 NICU nurses working in a training and research hospital. A Descriptive Data Form, a voice recorder and a Semi-structured Interview Form were used in the data collection. Content analysis was performed to assess the qualitative data. COREQ (COnsolidated criteria for REporting Qualitative research) checklist was used in reporting the research. The participants’ statements were analyzed and sorted out under 4 themes. Results The themes were noise awareness, noise prevention methods, unavoidable noise sources, and quiet. It was found that nurses in the NICU were aware of the sources of noise in the unit, protected the neonates from the effects of the various sounds by using sound reduction methods, and consequently observed the positive effects of these techniques on neonatal health and wellbeing. Implications for Practice: This study revealed that nurses were knowledgeable and practise in different noise prevent about methods to prevent noise in the NICU. Implications for Research: May enable the creation of standardized checklists for the NICU’s noise suppression program. Clinical Trial Number Not applicable. This research is a qualitative study.